Resource-Based and Institutional Perspectives on Export Channel Selection and Export Performance - He, Xinming; Brouthers, Keith D.; Filatotchev, Igor (Journal of Management, 2013)
Exporting is a critically important strategy for firms to grow, yet research in this area has tended to ignore how firms can leverage resource-based capabilities to improve export performance. Building on the resource-based view and institutional theory, the authors develop a novel perspective to explain how a firm can improve export performance by aligning its export channel with its level of market orientation capabilities, contingent on the institutional distance between home and export markets. Using a unique database of Chinese exporters, the authors find that exporters with strong market orientation capabilities prefer hierarchical export channels, while those with weak market orientation capabilities prefer hybrid channels. The analysis also indicates that the institutional distance between China and the export market moderates this relation. Moreover, the authors find that aligning export channel choice with firm-level market orientation capabilities and institutional distance yields better export performance.